Does self-esteem mediate the relationship between stress and exercise addiction? - Soraci, Paolo; Pisanti, Renato; Servidio, Rocco Carmine; Lo Destro, Calogero; Melchiori, Francesco Maria; La Rocca, Annalisa; Di Bernardo, Carla; Szabo, Attila (Psychology Hub, 2024)
Background: The risk of exercise addiction is generally associated with high levels of stress and low self-esteem. Previous studies have revealed a significant association between stress, risk of exercise addiction, and self-esteem. However, the mediating effect of the latter was not examined. Aims: Based on the Interactional Model of Exercise Addiction, we hypothesized that stress might influence the risk of exercise addiction through the mediating role of self-esteem. Method: This cross-sectional study used a convenience sample of 200 Italian exercisers aged 18 to 69 (M = 35; SD = 4.05; 62% females). Participants completed demographic and exercise habits-related questions, the revised Exercise Addiction Inventory, Stress subscale of DASS-21, and the Rosenberg’s Self-Esteem Scale in an online survey. Results: A positive association was found between stress and the risk of exercise addiction. However, a negative association emerged between stress and self-esteem. Furthermore, self-esteem was also related negatively to the risk of exercise addiction. Notably, self-esteem partially mediated the association between stress and the risk of exercise addiction. Conclusions: Self-esteem plays a role in the stress and exercise addiction relationship. Overall, the results contribute to a better understanding of the complex set of mechanisms that underlie the effects of stress on exercise addiction.